Effects of climate change on pup growth and survival in a cooperative mammal, the meerkat. (13th November 2019) - Van de Ven, Tanja M. F. N.; Fuller, Andrea; Clutton‐Brock, Tim H.
Abstract: Breeding systems in which group members help to raise the offspring of co‐members are associated with arid, unpredictable environments. Cooperative rearing may mitigate the effects of adverse environmental conditions on pup growth and survival. However, few studies have explored the relationship between environmental variation and breeding success, and the role of helpers. Here, we show that reductions in the growth and survival of meerkat ( Suricata suricatta ) pups have been associated with increases in daily maximum air temperatures ( T max ) in the southern Kalahari over the last 20 years. On days when T max was high, meerkat pups gained less body mass than on cooler days. Reductions in the diurnal body mass gain (Δ M b ) of pups on hotter days were not a consequence of reductions in the frequency with which pups were fed by adults as feeding rate increased with T max, suggesting that the reductions in Δ M b by pups on hot days reflected a decrease in water content of the food items or an increased water and energy cost of thermoregulation. Reductions in pup Δ M b on hot days were smaller in larger groups, in which helper‐to‐pup ratios were relatively high. As increases in air temperature are predicted with climate change, further reductions in meerkat pup growth and survival seem inevitable. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.